The little book of Investing like the pros : five steps for picking stocks - Pearl, Joshua, 1981-; Rosenbaum, Joshua, 1971- (Little book series, 2020)
"As you have probably noticed, there are quite a few investing books out there. Many of them were written by some of the world's greatest investors. So, why should you read our book? Stock investing is more prevalent than ever, whether directly or indirectly through brokerage accounts, exchange-traded funds (ETFs), mutual funds, or retirement plans. Despite this, the vast majority of individual investors have no training on how to pick stocks. And, until now, there hasn't been a truly accessible, easy-to-understand resource available to help them. The Little Book of Investing Like the Pros was written to fill this void. We believe the simplicity and accessibility of our stock picking framework is truly unique. Using real-world examples and actual Wall Street models used by the pros, we teach you how to pick stocks in a highly accessible, step-by-step manner. Our goal is straightforward; to impart the skills necessary for finding high-quality stocks while protecting your portfolio with risk management best practices. Our practical approach is designed to help demystify the investing process, which can be intimidating. This training will help set you apart from others who are largely flying blind. Pilots require extensive training before receiving a license. Doctors must graduate medical school, followed by a multi-year residency. Even those providing professional investment advice require certification. But, anyone can buy a stock without any training whatsoever. While buying stocks on a hunch and a prayer may not endanger your life, it can certainly put your finances at risk"--